AI in Financial Services: Revolutionizing Fraud Detection and Risk Management - Swapna Reddy Anugu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the transformative impact of artificial intelligence and machine learning technologies on financial institutions' approaches to fraud detection, risk management, and regulatory compliance. The article explores how cloud-powered AI solutions are revolutionizing security measures and operational efficiency in the financial sector. From advanced fraud detection systems to automated regulatory compliance, the article demonstrates how AI-driven solutions are enabling financial organizations to enhance their security posture while streamlining operations. The article covers the evolution of financial security systems, core components of AI-driven security, technical implementation considerations, and regulatory compliance integration, concluding with an examination of emerging trends shaping the future of AI-powered financial security.
Keywords: Artificial Intelligence; Financial Security; Fraud Detection; Regulatory Compliance; Risk Management